The Effect of The Education and Training Program of Continuous Professional Development Program of In On In Modes on Pedagogical and Professional Competence of Teachers in Kendal - Prihidayanti, Yayuk; Florentinus, Totok Sumaryanto; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2019)
Teacher professional development training is carried out by the government to improve the pedagogical and professional competence of teachers in learning KK A and B modules through in on in mode. This study has the purpose of determining the effect of the continuous professional development of in on in mode toward the pedagogical and professional competence of the elementary school teachers in Kendal Regency. This study was conducted using quantitative research methods of experimental post-test only control design t-test. The experimental group was given treatment, and the control group did not participate in the continuous professional development program in on in model, which was then given a post-test with the same questions. The results showed that there were differences in the pedagogical competencies with a significant value of 0.002 and differences in professional competence with a significant value of 0.001. Based on these results, it can be concluded that the continuous professional development program in on in mode affects the pedagogical competence. However, it does not affect professional competence. By increasing the teacher competence, it will affect the quality of the world of education for students, schools, a country in general and personal matter of teachers in particular. Training that can measure the results of activities based on their preparation, process and evaluation that can improve teacher competence in the field of linguistics needs to be carried out.